(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
The following study reports the preliminary results of an investigation into the reading experiences of students entering the Pedagogy program in Spanish Language and Communications at a state university in southern Chile. The objective was to know and characterize the reading capital and the motivations that students have towards reading, understanding by reading capital, the collection, and repertoire of works of literature reported by the students, and by motivations towards reading, the impulse that actively directs behavior towards achieving an objective as a reader (Aragón and Arias, 2013). The research was developed from the qualitative paradigm. Surveys, semi-structured interviews, and focus groups with two cohorts of students were used to collect data. Data processing was carried out through content analysis, establishing categories derived from the speeches and testimonies of the study subjects. The findings reveal the diversity of inherited cultural capital and coincidences between cohorts concerning the importance of literature in the development of imagination and creativity.